Open Source Software adaptation in Africa: is a matter of inferior or cheap is not quality? - Bakar, Abubakar Diwani; Md. Sultan, Abu Bakar; Zulzalil, Hazura; Din, Jamilah (IGI Global, 2014)
The African continent has long benefited from adopting OSS in its private and public organizations that have changed their way of development, the use and how to acquire proprietary software. This frequency of adaptation does not appear to be in balance with the contribution to the OSS community. Using views from experienced software practitioners working in different organizations across two African countries it has been observed that neglected infrastructure, a wide availability of proprietary software and misconceptions of a clear meaning of Open Source Software across Africa have been an obstacle towards the participation in the OSS technology in the global network.